2015
DOI: 10.1140/epjb/e2015-60213-4
|View full text |Cite
|
Sign up to set email alerts
|

Finite temperature effective field theory and two-band superfluidity in Fermi gases

Abstract: We develop a description of fermionic superfluids in terms of an effective field theory for the pairing order parameter. Our effective field theory improves on the existing Ginzburg -Landau theory for superfluid Fermi gases in that it is not restricted to temperatures close to the critical temperature. This is achieved by taking into account long-range fluctuations to all orders. The results of the present effective field theory compare well with the results obtained in the framework of the Bogoliubov -de Genn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(104 citation statements)
references
References 70 publications
7
97
0
Order By: Relevance
“…In particular, it is no longer admissible to treat the closed channel state as a single boson without taking into account of its proper internal dynamics. One is thus lead to a situation much the same as a two-band superconductor, where the appropriate picture is that two Fermi surfaces (including both spin) intersect the chemical potential [18][19][20]. We show that this new situation leads to the appearance of new collective modes and in particular, the long-sought Leggett mode in the two-band superconductor.…”
mentioning
confidence: 89%
“…In particular, it is no longer admissible to treat the closed channel state as a single boson without taking into account of its proper internal dynamics. One is thus lead to a situation much the same as a two-band superconductor, where the appropriate picture is that two Fermi surfaces (including both spin) intersect the chemical potential [18][19][20]. We show that this new situation leads to the appearance of new collective modes and in particular, the long-sought Leggett mode in the two-band superconductor.…”
mentioning
confidence: 89%
“…Hence, results found in this regime should be treated with additional caution. A second remark that must be made is that in the full version of the EFT, as it was introduced in [21], the action functional (1) contains additional terms that result in terms with second order time derivatives (SOTDs) of the pair field in the equation of motion (9) (with a form similar to the terms for the spatial derivatives). While it would in principle be better to use the full SOTD model, we found that numerical SOTD simulations of soliton-soliton collisions exhibit inherent instabilities in a large area of the parameter domain.…”
Section: Validity Of the Modelmentioning
confidence: 99%
“…In order to obtain the corresponding dispersion relation ω(q), we determine the wavelength λ i (measured as the distance between two consecutive peaks) and the velocity v i of each matter wave and apply the relations q i =2π / λ i and ω i =q i v i . The resulting dispersion of the oscillations can then be compared to the spectrum ω s (q) of the collective excitations of the superfluid, which in the context of the present EFT is determined by calculating the poles of the inverse propagator for the bosonic fluctuations [21]. Up to fourth order in q, this leads to the form…”
Section: Dispersion Of the Density Oscillationsmentioning
confidence: 99%
“…Consequently the use of the BdG theory is mainly limited to the consideration of zero-temperature properties of single-vortex states [10][11][12] . Because of this big computational cost of the BdG theory, there is a recent interest in the development of effective field theories [20][21][22][23][24][25][26] . These effective field theories allow for a description of non-uniform excitations (e.g.…”
Section: Introduction: Vortices In the Bec-bcs Crossovermentioning
confidence: 99%